Stitch bond strength study in insulated Cu wire bonding - Leong H.Y.; Yap B.K.; Khan N.; Ibrahim M.R.; Tan L.C.; Faiz M. (Maney Publishing, 2023)
The market demands for higher pin counts and more chips functionality pose challenges in conventional wire bonding. However, insulated Cu wire technology enables fine and ultra-fine pitch wire bonding as the insulator coating on the bare wire prevents wires shorting problem. This paper presents the study on the stitch-bonding process optimisation and its challenges for the insulated Cu wire with a diameter of 20 ?m. Insulated Cu stitch bond samples show 37% lower stitch pull strength than that of bare Cu. The cross-sectioned insulated Cu stitch bond shows that there is an insulation residue between the Cu stitch and the Au-plated substrate, potentially resulting in lower stitch pull performance. However, after isothermal aging at 225°C for up to 78 hours, the stitch pull results for insulated Cu wire passed the industry reliability standard, without any lifted bond. A detailed comparison study was performed for the insulated Cu and the bare Cu stitch bonding. © 2014 W. S. Maney & Son Ltd.